Pick me : a novel - Schade, Victoria (Avon A, an imprint of HarperCollins Publishers, 2025)
Romance writer Brooke Murphy is feeling fresh out of hot and steamy vibes. With a deadline looming and desperate for inspiration, she says "yes" to every romantic opportunity including playing a pickleball mixed doubles game with a handsome partner. To impress him, she starts taking lessons from a grumpy coach who doesn't look like an elite athlete. But as her game improves, she begins to wonder if she's falling for her coach instead of her partner.